Dyslipidemia In Patients Whith Rheumatoid Arthritis - عبد الرزاق حسن; يوسف زريق; لميس حيدر (Latakia University Journal -Medical Sciences Series, 2022)
Background: Rheumatoid arthritis is one of the most common chronic inflammatory arthritis , inflammatory process doesn´t involve only the joints but it may include other extra articular manifestation . Patients whith Rheumatoid arthritis have higher risk of cardiovascular disease than others and atherosclerosis is the most common cause of death , dyslipidemia caused by chronic inflammatory process is considered one of the most important cardiovascular risks , so this research aims to investigate dyslipidemia in these patients to reduce morbidity and mortality. The goal of the study: to determine the frequency of dyslipidemia in patients whith Rheumatoid arthritis , evaluate the relation between lipid profile and disease activity score (DAS 28) and classification dyslipidemia according the type of treatment using in manengement Rheumatoid arthritis. Methods: An observational cross sectional study included 80 patients fulfilling the ACR-EULAR 2010 criteria for RA . clinical assessments were performed by evaluation of disease activity score (DAS 28) and laboratory investigations of lipid profile including triglycerides (TG),total cholesterol (TC) ,low density lipoprotein (LDL)and high density lipoprotein (HDL) were performed . Results and discussion: the mean age was 52.9±12.4 years and the mean duration of disease was 12±8.8 years . 67.5 % of patients had dyslipidemia ,and the commonest abnormality was a low HDL ,seen in 40 % , raised TG was found in 37.5% raised TC was found in 15% and raised LDL was found in 10 % of the patients . Dyslipidemia was found in 84% of patients under treatment whith prednisolone , 81% in patients under treatment whith prednisolone and leflonomide ,75 % in those whith no treatment ,64.3 % in patients under treatment whith prednisolone and methotrexate and 57.1% in patients under treatment whith prednisolone and methotrexate and anti malaria. results also show that patients under treatment whith prednisolone had higher concentrations of HDL than those not treated (p value= 0.047). DAS 28 showed high negative correlation whith HDL(R= - 0.69), moderately positive correlation whith TG (R= o.475),high negative correlation whith TC (R= - 0.629) and moderately negative correlation whith LDL (R= - 0.552).